Analisa Pemampatan Tanah Subgrade Jalan Baru Universitas Islam Nahdlatul Ulama Jepara - Yayan Adi Saputro (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
The road construction implementation plan must be supported by supporting parameters such as the plan for the construction of a new road at the Islamic University of Nahdlatul Ulama Jepara. One of the supporting parameters is conducting subgrade testing. Usually subgrade tests for roads use several tests to obtain CBR values. However, this study examines soil compression that will occur when loading is carried out. The type of testing performed is a consolidation test in the laboratory. The result of this test is the Compression Index (Cc) value of laboratory Cc = 0.8305. The pre-consolidated stress (Pc) Pc (the maximum stress that the soil has experienced in the past) = 4.8 kg / cm2. P0 (current stress experienced by the soil) = 0.0773 kg / cm2. OCR = 64.6557. Pc> P0 so that the soil from this laboratory test is Over Consolidated. At a load of 0.5 kg get a value of Cv 0.024, a load of 1 kg get a value of Cv 0.048, a load of 4 kg get a value of Cv 0.444, and a load of 8 kg get a value of Cv 0.177. Recompression Index (Cr) Value of laboratory Cr = - 0.4152